Analysis of ERP implementation system at a Japanese medical device company - Umemoto, Haruna (2022)
This case study examines the qualitative and quantitative methods used to analyze the factors that led to the failure of ERP implementation system of Japanese Medical Device Company, as well as what kind of recommendations could be made for the management decisions made at that time. Based on the findings from the interviews and data collection, this case study seeks to examine the decision-making process at the company and the circumstances surrounding the Japanese company that led to the decision.